Issues of the diagnostic and treatment of generalized pustular psoriasis - Violetta A. Kovtunova; Sergey A. Altukhov; Ludmila P. Voronina; Elvira G. Bakhmutova; Olga V. Zhizhimova (LLC "MEDIAFORMAT", 2024)
Generalized pustular psoriasis (GPP), being a chronic inflammatory systemic disease, significantly reduces the quality of life of patients, leads to disability and increases the risk of mortality. Representing one of the most severe variants of the disease, GPP has its own features of pathogenesis, which distinguish it from plaque and other forms of dermatosis. Presently, the key factor in the development of the systemic process in GPP is considered to be a decrease in the expression or activity of IL-36ra receptor antagonists due to mutation of the IL-36RN gene, and as a result of this, excessive activity of IL-36 agonists and accumulation of neutrophil granulocytes in the epidermis. Based on the features of clinical manifestations in the form of multiple painful pustules accompanied by fever up to 40° C, characteristic changes in laboratory parameters in the form of increased markers of inflammation (leukocyte levels with neutrophil shift in peripheral blood, C-reactive protein), GPP needs to be differentiated from a number of diseases accompanied by similar symptoms: subcorneal pustular dermatosis Sneddon-Wilkinson, Sweet's syndrome, a herpes infection. The features of the pathogenesis of GPP determine the difficulties in the treatment of medicines that are successfully used in the treatment of plaque psoriasis, including methotrexate, cyclosporine, retinoids, TNF-α inhibitor, interleukin-17 and -23 inhibitors, as well as their combinations. A clinical case of a severe continuously recurrent resistant to therapy with cytostatics and genetically engineered preparations is presented, the diagnosis of which was complicated by a contradictory pathomorphological picture.